Love's Paradox: Unraveling the Dynamics of Love and Psychological Intimate Partner Violence Against Women - Ablana, Cécylia (Violence against women, 2026)
This study investigates the connection between psychological intimate partner violence (IPV) and love components in relationships, surveying 1,061 women. Using Sternberg's Triangular Love Scale, participants assessed Intimacy, Commitment, and Passion, revealing four clusters (“Moderate Love,” “No Love,” “Low Passion,” and “Mostly Passion”). ANCOVA (analysis of covariance) analysis, with age as covariate, highlighted significant differences in Intimacy, Commitment, and Passion among clusters, validating the classification. Surprisingly, the “Mostly Passion” cluster exhibited higher severe psychological aggression and specific controlling behaviors than the “Low Passion” group. These findings emphasize the intricate relationship between love components and psychological IPV, suggesting tailored interventions for healthier relationships and victim support.